The Assessment of Indoor Thermal Comfort Of University Classrooms in Hot and Humid Area - Rahmi Andarini; Muhammad Dzaky Al-Haidar; Vincentius Rayza Lee (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2025)
Thermal comfort is a description of the mental satisfaction experienced by humans regarding the temperature conditions in the surrounding environment. Appropriate thermal comfort conditions will have a positive influence on the occupant such as increasing productivity. This research was carried out to determine the level of thermal comfort in classrooms of the Universitas Multimedia Nusantara. There are two methods applied in this study, firstly by measuring indoor air quality parameters, and the second method is by surveying the occupants' acceptance of the indoor air condition. The measurement of indoor air parameters consists of two different methods, those are by installing Internet of Things monitoring systems, and manual measurement. There were 2 classrooms and 1 student lounge surveyed, and the measured parameters were indoor air temperature and relative humidity. The results of the measurements show that the average indoor air temperature of the conditioned classrooms was 26OC and the average temperature of the student lounge during unconditioned was 29OC. With the same condition, the measured relative humidity in the classrooms was found at 55% and the student lounge was at 70%. Regarding the thermal comfort condition, 68% of occupants of Student Lounge felt just comfortable,17% felt very comfortable and 15% felt uncomfortable. The opinion regarding this choice is affected by the sitting position of the respondents. At the classrooms D1509 and D1510, 64% of the respondents felt just comfortable, 28% felt very comfortable, 8% felt uncomfortable, which means that the majority of the respondents felt comfortable.